The realization of fourth-order rational transfer functions with adjustable coefficients - Paul, R. J. A. (College of Aeronautics, 1963)
Design techniques are described for the simulation of third-order and fourth-order rational transfer functions with adjustable coefficients. The realization procedure, which is based on the use of an ideal computing amplifier associated with linear passive R.C. two-port networks, is an extension of the methods described previously(1,2) for quadratic functions.